2008
DOI: 10.1590/s1982-56762008000200009
|View full text |Cite
|
Sign up to set email alerts
|

Fosfito de potássio e ulvana no controle da mancha foliar da gala em macieira

Abstract: . C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
20

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
1
7
0
20
Order By: Relevance
“…Silicon can therefore interact with several key components of the plant stress response-related signaling pathways, leading to effective resistance to pathogenic fungi. In agreement with the results of our study, Araújo et al (2008), while studying Colletotrichum gloeosporioides, showed that potassium phosphite (Fitofós K®) has a direct effect on this fungus, almost completely inhibiting the mycelial growth in vitro. Potassium phosphite was tested against Penicillium expansum, which causes postharvest blue mold infections on apple fruits; this compound completely inhibited the mycelial growth (Amiri and Bompeix, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Silicon can therefore interact with several key components of the plant stress response-related signaling pathways, leading to effective resistance to pathogenic fungi. In agreement with the results of our study, Araújo et al (2008), while studying Colletotrichum gloeosporioides, showed that potassium phosphite (Fitofós K®) has a direct effect on this fungus, almost completely inhibiting the mycelial growth in vitro. Potassium phosphite was tested against Penicillium expansum, which causes postharvest blue mold infections on apple fruits; this compound completely inhibited the mycelial growth (Amiri and Bompeix, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…and can reduce the severity of a broad range of diseases on beans, such as rust (Uromyces appendiculatus (Persoon) Link) (Borsato et al, 2010;Delgado et al, 2013), anthracnose (C. lindemuthianum) (Paulert et al, 2009;Freitas & Stadnik, 2012) and powdery mildew (E. poligoni) (Jaulneau et al, 2011). In addition, the polissaccharide has shown promising results against other diseases such as Glomerella leaf spot (C. gloeosporioides (Penzig) Penzig and Saccardo) on apple (Araújo et al, 2008;Araújo & Stadnik, 2013) and powdery mildew (Blumeria graminis (DeCandole) Speer) on wheat and barley (Paulert et al, 2010;Jaulneau et al, 2011). The effects of ulvan in different pathosystems are shown on Table 1.…”
Section: Ulvansmentioning
confidence: 99%
“…Devido à influência da idade na suscetibilidade a MFG, as folhas superiores foram escolhidas, pois estas são mais suscetíveis do que as inferiores, mais velhas (Araújo et al, 2008). Os discos foliares coletados para análise microscópica foram processados conforme metodologia descrita por Araújo e Stadnik (2011).…”
Section: A Mancha Foliar De Glomerella (Mfg) Causada Porunclassified